Case Report: An NTRK1 fusion-positive embryonal rhabdomyosarcoma: clinical presentations, pathological characteristics and genotypic analyses - Li, Na-Mei; Jiang, Shi-He; Zhou, Peng; Li, Xiao-Hong (Frontiers in Oncology, 2023)
Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma of children. Pediatric RMS occurs as two biologically distinct histological variants, embryonal (ERMS) and alveolar (ARMS). ERMS is a primitive, malignant, soft tissue sarcoma that recapitulates the phenotypic and biological features of embryonic skeletal muscles. With the increasing application of next generation sequencing (NGS) and other molecular biological detection technologies, it has been possible to determine the oncogenic activation alterations of many tumors, such as those related to tyrosine kinase. Specifically for soft tissue tumors, the determination of tyrosine kinase gene and protein related changes can be used as diagnostic aids and may be used as predictive markers for targeted tyrosine kinase inhibition therapy. We present a case of an 11-year-old patient with ERMS. He was found to be positive for MEF2D-NTRK1 fusion. This unique case report highlights the clinical, radiographic, histopathological, immunohistochemical and genetic findings of a palpebral ERMS. It also demonstrates a rare case of ERMS sarcoma with NTRK fusion, which has not been previously reported in the literature.